2023
DOI: 10.1002/cam4.6364
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mortality burden in patients with cancer due to COVID‐19 in the US: A national cross‐sectional analysis

Abstract: IntroductionThere is limited information on the impact of certain social factors on mortality outcomes in patients with cancer and COVID‐19 on a national scale. This study aims to characterize excess mortality and analyze a subset of sociodemographic trends in COVID‐19 and cancer mortality.MethodsPatients with cancer listed on their death certificates from 2018 to 2021 and patients with COVID‐19 and cancer listed on multiple cause of death certificates from the CDC Wide‐Ranging Online Data for Epidemiologic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Mortality rates of cervical and uterine cancers were higher in black women than in those of other races during the study period. This goes in line with known findings which showed that age-adjusted mortality rates in patients with cancer and COVID‐19 were found to be significantly higher in NH Black or African American, Hispanic or Latino, and NH American Indian or Alaskan Native groups in 2020 [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Mortality rates of cervical and uterine cancers were higher in black women than in those of other races during the study period. This goes in line with known findings which showed that age-adjusted mortality rates in patients with cancer and COVID‐19 were found to be significantly higher in NH Black or African American, Hispanic or Latino, and NH American Indian or Alaskan Native groups in 2020 [ 14 ].…”
Section: Discussionsupporting
confidence: 90%